Efficacy of Oral Azithromycin Versus Doxycycline in Treatment of Meibomian Gland Dysfunction - Koirala, Ashesh; Bhattarai, Samiksha; Shah, Sangeeta; Shrestha, Bhuwan Govind; Lavaju, Poonam (Nepalese Journal of Ophthalmology, 2024)
Introduction: Meibomian gland dysfunction (MGD) is usually treated with conservative methods. Adjunct therapy with oral Doxycycline has played a vital role in its treatment. Recently Azithromycin has also been introduced as a newer agent. Objective: To compare the efficacy, safety and compliance of oral azithromycin with doxycycline over one year period in patients with Meibomian gland dysfunction (MGD). Methodology: A randomised comparative clinical trial was performed among 284 subjects (age >35 years) with MGD. They were randomly divided into two groups A and B. Along with standard conservative management, Group A received oral 9-day azithromycin (500 mg for 3 consecutive days for 3 consecutive weeks) and group B received 14 days doxycycline (200 mg/day). A score comprising seven symptoms and seven signs (primary outcome) was recorded before and at first and second follow up after treatment and further analyzed. Result: The mean symptoms and signs treated by Azithromycin group was lesser as compared to Doxycycline group in the first follow up (p <0.001). However it was statistically insignificant at second follow-up (p=0.043). The group taking azithromycin had a much better overall response (p = 0.006). Gastrointestinal symptoms were the major side effects encountered, the group taking doxycycline experienced significantly more side effects (p ≤0.001). Conclusion: Both antibiotics were effective and safe for treating persistent MGD, but azithromycin was more effective. It required a lower dose, worked faster, and had a shorter treatment duration compared to doxycycline.